A novel electrochemical sensor for glucose detection based on a Ti3C2Tx/ZIF-67 nanocomposite. Issue 31 (12th July 2022) - Han, Xuhui; Cao, Ke; Yao, Yanqing; Zhao, Jia; Chai, Chunpeng; Dai, Pei
Abstract : A Ti3 C2 T x /ZIF-67 nanocomposite with outstanding conductivity has been prepared. The electrochemical sensor based on this nanocomposite exhibits excellent selectivity, stability and repeatability for glucose detection. Abstract : A Ti3 C2 T x /ZIF-67 nanocomposite with outstanding conductivity has been prepared by loading ZIF-67 onto a two-dimensional Ti3 C2 T x nanosheet. Ti3 C2 T x sheets were synthesized by etching Ti3 AlC2, and then ZIF-67 was grown in situ on the Ti3 C2 T x nanosheet. The Ti3 C2 T x /ZIF-67 nanocomposite exhibits excellent detection performance for glucose, with a low LOD of 3.81 μM and wide linear detection range of 5–7500 μM. This terrific result is contributed by the synergistic effect of the high electrically conductive ability of Ti3 C2 T x and active catalytic performance of ZIF-67. Moreover, the electrochemical sensor prepared using the Ti3 C2 T x /ZIF-67 nanocomposite also shows excellent selectivity, stability and repeatability for glucose detection. The Ti3 C2 T x /ZIF-67 nanocomposite with outstanding performance has potential applications for electrochemical sensors.